2012
DOI: 10.2478/v10265-012-0042-4
|View full text |Cite
|
Sign up to set email alerts
|

Light Pollution of the Mountain Areas in Poland / Zanieczyszczenie Świetlne W Obszarach Górskich W Polsce

Abstract: Abstract:The existence of extensive records for the impact of night sky brightness on the animals' behavior in their natural environment shows the need to investigate the level of artifi cially induced night sky glow (light pollution) in the protected areas.The results of multi-night sky brightness measurements carried out at the selected sites in Polish mountain areas under various atmospheric conditions are presented. Conducted measurements show a strong impact of the artifi cial sky glow on the night sky br… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(6 citation statements)
references
References 13 publications
0
6
0
Order By: Relevance
“…The issue of the clarity of the night sky is a complex issue and goes beyond the scope of this paper. However, when analyzing the works which present the measured values of the brightness of the night sky [24], it can be stated that luminance in summertime usually does not exceed 0.005 cd/m 2 . Thus, in further considerations, the curve V'(λ) is considered when assessing the light pollution of the night sky.…”
Section: Simulation Results and Their Analysismentioning
confidence: 99%
See 1 more Smart Citation
“…The issue of the clarity of the night sky is a complex issue and goes beyond the scope of this paper. However, when analyzing the works which present the measured values of the brightness of the night sky [24], it can be stated that luminance in summertime usually does not exceed 0.005 cd/m 2 . Thus, in further considerations, the curve V'(λ) is considered when assessing the light pollution of the night sky.…”
Section: Simulation Results and Their Analysismentioning
confidence: 99%
“…In general, the number of works devoted to the influence of SPD on the effect of light pollution is significant [11,[23][24][25][26][27][28][29][30][31][32][33]. Within these studies, there are many works in which analysis of the influence of SPD on light pollution effect is extended by consideration of spectral reflectance of the ground or atmosphere properties.…”
Section: Introductionmentioning
confidence: 99%
“…The most important change was the use of remote data transfer in the measurement process, which reduced the time, organisational and logistical constraints prevalent when using the manual method for such a large area, and also in uenced the daily repeatability and comparability of the measurements carried out. This is because the phenomenon of light pollution is characterised by variability depending not only on the phase of the moon, but primarily on the prevailing atmospheric conditions and air quality [8,10]. On cloudless and overcast nights, the measurements obtained do not differ signi cantly from each other, while on nights with changing cloud cover, the results can differ signi cantly, as cloud cover considerably affects the night sky brightness measurements.…”
Section: Stages Of the Project Implementationmentioning
confidence: 99%
“…The phenomenon is aggravated by the presence of illuminated advertising neon signs and excessive backlighting of architectural elements and city illuminations. In addition, research has shown that light pollution is exacerbated by the scattering of arti cial light in the atmosphere by dust of anthropogenic origin present in the atmosphere, as well as being ampli ed by the re ection of light from clouds, especially low-and mid-level clouds [4][5][6][7][8][9][10].…”
Section: Introductionmentioning
confidence: 99%
“…In areas that are free from light pollution, the overcast sky is darker than the cloudless one, because the clouds obscure natural light sources, such as stars, planets and the Moon, without scattering any ground-based artificial lights. It was found that the shape of the curve representing the brightness of the night sky vs. the cloudiness is one of the best indicators of the level of light pollution [3]. This means that the ability to determine the presence of clouds in the sky and their possible genus is extremely important for the proper position assessment of astronomical observations.…”
mentioning
confidence: 99%